Final-Year Dental Students’ Perceived Confidence: Competencies in General Dentistry - Navodika Yaparathna; Iresha Udayamalee; Megan Gray; Cheree He; Rachel Wu; Chelsea Taing; Menaka Abuzar (Dentistry Journal)
Background: Competency in providing high-quality, comprehensive patient care is essential for newly qualified dentists. Dental curricula are designed to equip graduates with necessary skills to develop competencies. Outplacement training has been incorporated into most dental curricula to provide broader clinical experience in a real-world situation. Methods: This cross-sectional study aimed to assess (1) the perceived confidence of final-year dental students (FYDSs) at an Australian university with reference to the Australian Dental Council (ADC) professional competencies for newly qualified dentists; (2) the association between perceived confidence and the timing of outplacement training; and (3) students’ perceptions on outplacement training in developing their competencies. Two online surveys were administered to a cohort of FYDSs at the end of the first and second trimesters. ‘Survey 1’ was based on the ADC competency requirements (2022) and assessed aims 1 and 2. The five domains assessed were (1) communication and leadership; (2) critical thinking; (3) health promotion; (4) scientific and clinical knowledge; and (5) person-centred care. ‘Survey 2’ assessed students’ perception on outplacement training and was administered towards the completion of their outplacement to assess aim 3. Results: Students’ perceived competency levels were high across all domains. Those with prior tertiary education were more confident in communication and leadership, health promotion, and scientific and clinical knowledge than students with secondary qualifications. The perceived confidence in professional competencies among FYDSs had no significant association (p > 0.05) with the location or the sequence of outplacement. The thematic analysis of survey 2 responses reported the guidance and constructive feedback received from supervisors while managing cases in a real-life setup as a significant contributor to their confidence development. Conclusions: FYDSs reported a satisfactory level of perceived confidence in professional competencies. Both in-house training and outplacement equally improve the levels of competency development. FYDSs perceive outplacement training as a positive integral component in the development of skills.